Socio-Economic Factors as Determinant of Mobile Number Portability among Mobile Phone Users in Public Universities in Nigeria. - Akeke, Niyi Israel; Ajayi, Omobola Monsura (Archives of Business Research, 2018)
Mobile number portability is the window for subscriber to move to another network provider when not satisfied, but still keep his/her number. Specifically, the study evaluated the relationship between socioeconomic factors and intention to port among mobile phone users in public universities in Nigeria. The study covered twelve (12) public owned Universities in Southwest Nigeria; Primary data were collected on socio-economic of respondent using structured questionnaires. Descriptive and inferential statistics were used to analyze the data. Descriptive statistics include frequency counts and simple percentages, while inferential statistics such as logistic regression were used. The findings revealed that among all the variables, expenditure on recharge, income and duration of use were significant at (p< 0.05). These findings lead to further conclusion that younger consumers are more likely to port than older ones. The results also provided empirical support for linkages between socioeconomic factors, their subcomponents and mobile number compatibility among consumers.